Barriers to coastal planning and policy use of environmental research in Aotearoa-New Zealand - Hewitt, Judi E.; Lundquist, Carolyn J.; Pilditch, Conrad A.; Thrush, Simon F.; Urlich, Stephen C. (Frontiers in Marine Science, 2022)
Identifying barriers to the effective use of science in coastal management of Aotearoa-New Zealand is easy, due to the present lack of complicated governance and management structures, coupled with an emphasis on funding science that includes pathways to implementation. This opinion piece discusses four areas that still hinder effective use of science, all of which are likely to be problematic for other countries. We initially focus on why the science may not be used related to: misunderstandings (linguistic and conceptual differences including indigenous world views); timing of information delivery; uncertainty surrounding the information (knowledge limitations and funding); and top-down constraints (legal systems, politics and institutional objectives). We use Aotearoa-New Zealand examples to demonstrate the barriers operating within each area and discuss three potential solutions. Importantly our analysis indicates that researchers alone cannot transcend these barriers; rather, we need to work as part of an ecosystem, requiring commitment from all society, extending beyond the usual suspects (management agencies). We believe that ecological and systems education from junior school levels through to universities have an important role to play in setting the context to overcome current barriers.